2019
DOI: 10.1016/j.measurement.2019.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Development of a finger adapter method for testing and evaluating vibration-reducing gloves and materials

Abstract: The objective of this study was to develop a convenient and reliable adapter method for testing and evaluating vibration-reducing (VR) gloves and VR materials at the fingers. The general requirements and technical specifications for the design of the new adapter were based on our previous studies of hand-held adapters for vibration measurement and a conceptual model of the fingers-adapter-glove-handle system developed in this study. Two thicknesses (2 mm and 3 mm) of the adapter beam were fabricated using a 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The proposed requirements for the optimized design of the adapter are as follows: (i) the mass of the adapter and its tri-axial accelerometer should be as small as possible; (ii) the profile of the adapter should be as low as possible, and the accelerometer should be installed on the adapter as close to the contact surface as possible; (iii) the adapter configuration should allow for a sufficient force to be applied on the adapter to prevent separation of the adapter from its contact surfaces under vibration; (iv) the adapter should not change the original hand postures; (v) the vibration transmissibility measured with the accelerometer fixed on the adapter without coupling with the hand should be close to unity in the entire frequency range of concern (5 Hz to 1500 Hz) with a maximum error at <5%. Guided by these requirements, an adapter with a tri-axial accelerometer located between two fingers was developed [ 35 ], which is shown in Figure 2 . It has been successfully used to test and evaluate the vibration transmissibility of vibration-reducing gloves at the fingers.…”
Section: The Standard Methods For Measuring and Assessing Hand-transmitted Vibration Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…The proposed requirements for the optimized design of the adapter are as follows: (i) the mass of the adapter and its tri-axial accelerometer should be as small as possible; (ii) the profile of the adapter should be as low as possible, and the accelerometer should be installed on the adapter as close to the contact surface as possible; (iii) the adapter configuration should allow for a sufficient force to be applied on the adapter to prevent separation of the adapter from its contact surfaces under vibration; (iv) the adapter should not change the original hand postures; (v) the vibration transmissibility measured with the accelerometer fixed on the adapter without coupling with the hand should be close to unity in the entire frequency range of concern (5 Hz to 1500 Hz) with a maximum error at <5%. Guided by these requirements, an adapter with a tri-axial accelerometer located between two fingers was developed [ 35 ], which is shown in Figure 2 . It has been successfully used to test and evaluate the vibration transmissibility of vibration-reducing gloves at the fingers.…”
Section: The Standard Methods For Measuring and Assessing Hand-transmitted Vibration Exposurementioning
confidence: 99%
“…Their effectiveness has been systematically examined by measuring and modeling the glove vibration transmissibility using both to-the-hand and on-the-hand methods. The related studies include the following aspects: (i) Improving the methods and techniques for measuring the glove vibration transmissibility at the palm of the hand [ 52 , 155 158 ], which increased the accuracy and reliability of the testing results and contributed to a major revision of the VR glove test standard [ 42 ]; (ii) Developing a novel method for conveniently and reliably measuring the glove vibration transmissibility at the fingers [ 35 ], which may be included in the standard VR glove test in its future revision; (iii) Enhancing the understanding of the glove VR mechanisms and influencing factors through examining the correlation between the glove vibration transmissibility and the mechanical impedance of the hand–arm system [ 159 161 ], and developing computer models of the tool–glove–hand–arm system [ 53 , 77 , 162 ]; (iv) Measuring the glove transmissibility and investigating their influencing factors [ 44 , 54 , 62 , 163 ]; (v) Evaluating and applying a transfer function method to estimate tool-specific performance of the gloves [ 32 , 62 , 161 , 164 , 165 ]. The major conclusions made from these VR glove studies are as follows: (i) VR gloves may result in significant adverse effects such as increased hand fatigue and reduced finger dexterity because the gloves can increase the hand grip effort on a tool handle [ 141 ]; (ii) The available VR gloves do not usually reduce vibration transmitted to the hands at frequencies below 25 Hz; hence, it is better to use ordinary work gloves when operating low frequency tools such as rammers, tampers, and vibrating forks [ 164 ]; (iii) VR gloves can effectively reduce high frequency vibration components and sharp peaks [ 35 , 69 , 164 , 166 ]; (iv) Increasing the thickness of the glove cushioning materials and/or the suspended glove mass can increase the cushioning effectiveness of the glove but these changes can also increase the adverse effects of the glove [ 53 , 141 ]; hence, the current criteria for a certified anti-vibration glove require a limited thickness of the gloves; for these reasons, it may be difficult to improve the effectiveness of VR gloves from their current level by increasing their cushioning function; (v) Besides the cushioning function, a VR glove may also affect the finger or hand vibration through the other functions or factors of the glove [ 77 , 167 ]; for example, wearing a tight glove may increase the finger soft tissue stiffness due to the constraint of the glove material around each fin...…”
Section: Intervention Methods and Technologies For Controlling Hand-transmitted Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the frequency weighting to be adopted in order to evaluate the mean corrected transmissibility is still unclear, given that the FTV has both musculoskeletal effects (that would require the ISO 2631 [28] frequency weighting curves) and cardiovascular effects (that could be better described using the ISO 5349 weighting curve [29]). Furthermore, the current standard limitations, well evidenced by Dong and col-leagues [30], should be accounted also in the case of anti-vibration shoes.…”
Section: Comfort Associated With the Midsole/insole Materialsmentioning
confidence: 99%
“…Effect of a viscoelastic AV glove on the grip strength can be evaluated through measurements at the interface of the hand and the glove. Moreover, it has been suggested that effectiveness of the vibration reducing materials used in AV gloves can be enhanced through reduction in the fingers' contact force (Xu et al, 2019). The quantification of forces imposed by the fingers and the palm will necessitate applications of the force/pressure-sensing grid inside the glove between the hand and the glove.…”
Section: Introductionmentioning
confidence: 99%